Exploring the Roles of Parental Involvement in Enhancing Madrasah Education in the Philippines - Charlene C. Angkay (Faculty of Education and Teacher Training of UINSI Samarinda, 2025)
This study examines the important role of parental involvement in enhancing the effectiveness of Madrasah education in the Southern Philippines, particularly within the Arabic Language and Islamic Values (ALIVE) program. Despite its cultural importance, the program encounters challenges such as limited resources and cultural resistance that hinder its overall effectiveness. Understanding the level of parental engagement is crucial, as it significantly influences students' educational experiences. Utilizing a quantitative approach, this research employed stratified random sampling to survey 150 Muslim parents in General Santos City, although only 100 parents completed the questionnaires administered to them. Data were gathered through structured questionnaires, focusing on various aspects of parental involvement, including participation in school events, communication with teachers, and monitoring academic progress. The analysis revealed a high overall mean score of 4.70, indicating strong parental engagement in attending school events and participating in associations. However, lower scores in areas such as volunteering and communication with teachers present opportunities for improvement. These findings highlight the necessity of fostering collaboration between families and educational institutions to create a supportive learning environment. The study emphasizes the need for strategies that enhance parental involvement, ultimately leading to improved educational experiences for students in Madrasah settings. This research contributes valuable insights for improving educational practices and policies, emphasizing the need for strategies that enhance parental involvement to ultimately improve educational outcomes for students in Madrasah settings.